BAIBA Involves in Hypoxic Training Induced Browning of White Adipose Tissue in Obese Rats - Feng, Junpeng; Wang, Xuebing; Lu, Yingli; Yu, Chang; Wang, Xinyan; Feng, Lianshi (Frontiers in Physiology, 2022)
In recent years, obesity has become an important risk factor for human health; how to effectively prevent and reduce the occurrence of obesity is a hot research topic in recent years. Hypoxic training effectively improves abnormalities of lipid metabolism caused by obesity. The current study explored the effects of hypoxic training on BAIBA secretion and white fat browning in inguinal fat in obese rats. Analyses were performed by HPLC/MS/MS—MS/MS, RT-q PCR and western blot methods. The findings showed that 4 weeks of hypoxic training reduced body weight, Lee’s index, and regulated blood lipid profile in obese rats. Hypoxic training up-regulated BAIBA concentration in gastrocnemius muscle and circulation in obese rats. Hypoxic training significantly upregulated expression of PPARα and UCP-1 in inguinal fat of obese rats and increased white fat browning. The findings showed that BAIBA may involve in improveing blood lipid profile and white fat browning by modulating PPARα and UCP-1 expression.